Application of a compact trickle-bed bioreactor for the removal of odor and volatile organic compounds emitted from a wastewater treatment plant (2019)
A compact trickle-bed bioreactor (CTBB) was tested for the removal of volatile organic compounds (VOCs) and hydrogen sulphide (H 2 S) present in the exhaust air of a wastewater treatment plant. At gas-flow rates varying between 2.0 and 30.0 m 3 /h and for specific pollutant loads up to 20 g/(m 3 ·h), removal efficiencies for H 2 S and VOC were >95%. The CTBB was designed for a maximum H 2 S concentration of ~200 ppm and removal efficiencies >97% were noticed. VOC concentrations were in the range of 25–240 ppm v and the removal efficiency was in the range of 85–99%. Possible consequences of an excessive pollutant overload and the time required for regenerating the microbial activity and reviving stable process conditions in the CTBB were also investigated. An increase in the H 2 S concentration from 400 to 600 ppm v for a few hours caused bioreactor poisoning; however, when original H 2 S concentrations were restored, stable CTBB operation was ascertained within 3 h. © 2019 Elsevier Ltd